Impact of Coever Coaching Program on Learning Basic Skills of Football players under 15 years - CHERIET , Adel; BENSALEM, Salem (sports creativity, 2025)
The study aimed to reveal the impact of use of Coever Coaching Program to develop some basic skills of football (Passing and Receiving, running of the ball, shooting) among players under 15 years old. To achieve this research was conducted on a sample core of 20 players, were divided into two groups (experimental group and control group). The researchers used the experimental method. They used pre and post test for two sets. They used tests standardized measure basic skills of football players under 15 years. The researchers recommended in the light of what has been deduced from the results, attention should be paid to conduct scientific research through which the work of training programs related to improving and developing various basic skills of football players and link them to a high level, specially using the Coever Coaching Program on basic skills of football players under 15 years